(untitled) (Swiss Medical Weekly, 2017)
AIMS OF THE STUDY: We aimed to assess a potential association of iron status with mortality and morbidity of inpatients with systemic inflammation. METHODS This was a single centre prospective observational study. From April 2014 to October 2014, all consecutive medical inpatients aged ≥18 years with a C-reactive protein value >5 mg/l on hospital admission were eligible for the study. We excluded pregnant women and patients with terminal renal insufficiency or past allogeneic stem cell transplantation. For all patients, a complete set of serum iron parameters was obtained on hospital admission. In the final analysis, the in-hospital all-cause mortality and several morbidity measures (length of stay, number of secondary diagnoses and Charlson Comorbidity Index) were compared between four distinct iron status groups: patients having iron deficiency anaemia, iron deficiency without anaemia, anaemia without iron deficiency, and normal iron status. Iron deficiency was quantifies as the serum transferrin receptor / ferritin index, with a cut-off level of 1.5. RESULTS A total of 438 patients were included in the final analysis. Patients with iron deficiency had a higher in-hospital mortality than patients with iron deficiency anaemia, anaemia without iron deficiency, or normal iron status (6% vs 1%, 5%, and 1%, respectively; p = 0.042). Patients with iron deficiency anaemia had a higher number of secondary diagnoses (mean 8.4; standard deviation 4.2) and a higher Charlson Comorbidity Index (mean 1.8; standard deviation 1.9) than patients with iron deficiency, anaemia without iron deficiency, or normal iron status (p <0.001 and p <0.001, respectively). The median length of stay did not differ significantly between the iron status groups (p = 0.080). CONCLUSIONS In our study population, iron status was significantly associated with mortality and morbidity. Further studies are required to assess the pathophysiological and clinical effects of an altered iron metabolism and iron substitution therapies in inflammation. (ClinicalTrial.gov, NCT02155114).